Analysis of Secondary Metabolite Compounds and Sunscreen Potential of Red Seaweed Extract (Kappaphycus alvarezii) on the North Coast of Jepara - Susiloningrum, Dwi; Handayani, Yanulia; Nafi'ah, Lutfiana Nurulin (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Red seaweed (Kappaphycus alvarezii) or Eucheuma cottonii is one of seaweed that is widely cultivated by people in Jepara. Several studies stated that the seaweed has a lot of secondary metabolite content, one of them is Phenolic. It is known that these metabolites have potential to be used as sunscreen.The riserch is experimental and purpose of this study was to analyze secondary metabolite compounds and the sunscreen potential of red seaweed (Kappaphycus alvarezii) with solvent variations (70% ethanol, ethyl acetate and N-Hexane) using the Ultrasound Assisted Extraction (UAE) method. The average of total phenol content of 70% ethanol extract was 8.6%; ethyl acetate extract was 3.25% and N-Hexane extract was 5.23%. Sunscreen activity of red seaweed extract (Kappaphycus alvarezii) based on the highest SPF value in 70% ethanol extract with a concentration of 1000 ppm was 7.72 (extra protection). The best erythema transmission percentage (%Te) value in 70% ethanol extract with a concentration of 1000 ppm was 1.457% (extra protection). The best pigmentation transmission percentage (%Tp) value in 70% ethanol extract with a concentration of 1000 ppm is 3.21% (sunblock).